Mothering, Homemaking, and Studying: Indonesian Women Students in Australia - Sofkhatin Khumaidah (Fenomena, 2018)
Indonesian married women students who win scholarships to study in Australia face a complex challenge in reconciling their academic aspirations with domestic roles as mothers and wives, especially when bringing their families without domestic help. This study is grounded in the dominant gender order and patriarchal religious interpretations that assign women primary responsibility for homemaking and childrearing. The research aims to explore the lived experiences of these women in managing their dual roles as students and primary caregivers. Using a feminist standpoint methodology, this case study collected data through informal conversational interviews with Indonesian women students at Flinders University, South Australia. The findings reveal that internalized gender constructs significantly hinder women’s academic freedom, forcing them to avoid certain courses due to scheduling conflicts with domestic duties. Many participants consciously set aside professional and academic ambitions to fulfill perceived motherhood responsibilities. The study concludes that despite the physical and psychological benefits of family togetherness, the unequal gendered division of labor remains a major barrier. It is recommended that scholarship providers and universities offer flexible academic schedules and family support services, and further research should explore how male students balance family and study for comparative insights. Mahasiswi Indonesia yang sudah menikah dan mendapat beasiswa belajar di Australia menghadapi tantangan berat dalam menyeimbangkan ambisi akademik dengan peran domestik sebagai ibu dan istri, terutama ketika membawa keluarga tanpa bantuan pembantu. Penelitian ini berangkat dari konstruksi peran gender dominan dan interpretasi agama patriarkal yang menempatkan tanggung jawab pengasuhan anak dan rumah tangga pada perempuan. Tujuan penelitian ini adalah untuk mengeksplorasi pengalaman hidup para perempuan tersebut dalam menjalankan peran ganda sebagai mahasiswi dan pengasuh utama. Dengan menggunakan metodologi feminist standpoint, studi kasus ini mengumpulkan data melalui wawancara informal dengan mahasiswi Indonesia di Flinders University, Australia Selatan. Temuan penelitian menunjukkan bahwa konstruk gender yang telah terinternalisasi secara kuat menghambat kebebasan akademik perempuan, memaksa mereka menghindari mata kuliah tertentu karena benturan jadwal dengan tugas domestik. Sebagian besar subjek penelitian rela mengesampingkan ambisi profesional dan akademik demi memenuhi tanggung jawab keibuan. Kesimpulannya, meskipun kebersamaan keluarga memberikan manfaat psikologis, ketimpangan pembagian kerja gender tetap menjadi hambatan utama. Disarankan agar penyedia beasiswa dan universitas menyediakan jadwal akademik fleksibel serta layanan dukungan keluarga, dan penelitian lebih lanjut perlu mengkaji pengalaman mahasiswa laki-laki dalam menyeimbangkan keluarga dan studi.